Modernization of Atmospheric Physics Parameterization in Canadian NWP. (16th November 2019) - McTaggart‐Cowan, R.; Vaillancourt, P. A.; Zadra, A.; Chamberland, S.; Charron, M.; Corvec, S.; Milbrandt, J. A.; Paquin‐Ricard, D.; Patoine, A.; Roch, M.; Separovic, L.; Yang, J.
Abstract: Atmospheric physics is represented in numerical models by parameterizations that use resolved‐scale information to estimate the effects of physical processes on the atmospheric state. Over time, our understanding of these processes improves, new techniques are introduced to represent physics in a numerical model, and increased resolution changes the relative importance of different parameterizations within the system. As a result, the physical parameterization packages of numerical weather prediction (NWP) models undergo regular updates as older schemes are replaced with newer ones that offer an improved, and often more complex, depiction of relevant physical processes. Such changes are typically combined with a rebalancing of the physics suite because of strong interactions between parameterization schemes and the presence of compensating errors in the system. In this study, a major update to the package of physical parameterizations used in Canadian operational NWP is introduced. The primary goals of this effort were to improve the global energy budget and to facilitate an increase in the vertical resolution of operational configurations. Both of these objectives were achieved, along with a significant improvement in guidance quality for global and regional prediction systems. Key Points: An updated suite of parameterizations for atmospheric physics is developed for Canadian NWP Representation of the global energy budget is improved in the model climatology Significant improvements in guidance quality are seen in upper‐air, surface, and precipitation scores